The relationship of parity, education and maternal knowledge with complementary feeding at the Jeulingke Primary Health Center, Banda Aceh - Sofi Alfia Zuhra; Nora Sovira; Ima Indirayani; Jufitriani Ismy; Liza Salawati (AcTion: Aceh Nutrition Journal, 2025)
Inappropriate complementary feeding negatively affects children under two years. Parity, education, and maternal knowledge were associated with inappropriate complementary feeding. This study aimed to analyze the relationship between parity, education, and maternal knowledge of complementary feeding at the Jeulingke Primary Health Center in Banda Aceh, Indonesia. This analytical, observational study used a cross-sectional design. Data will be collected from September to October 2024 through interviews using questionnaires and 1 × 24-hour food recalls. This study included 76 mothers selected using consecutive sampling at seven integrated health service points in the Jeulingke Primary Health Center area. Statistical analysis was performed using Spearman’s test with a 90% confidence interval and an alpha level of 0.1. The study showed that 65.8% of the mothers provided appropriate complementary feeding practices. Parity was not significantly associated with complementary feeding (p = 0.194; r = -0.151). Maternal education (p = 0.049; r = 0.227) and knowledge (p = 0.028; r = 0.253) had weak relationships with complementary feeding practices. In conclusion, to implement appropriate complementary feeding, the education and knowledge of mothers as primary providers of complementary feeding at the Jeulingke Primary Health Center in Banda Aceh must be improved.